PENINGKATAN KETERAMPILAN MENULIS TEKS ANEKDOT DAN PRESTASI BELAJAR BAHASA INDONESIA DENGAN METODE INKUIRI PESERTA DIDIK KELAS X IPA 1 SMAN 3 METRO - Susnelly, Susnelly (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
Research purpose descriptive writes environment anekdot tex by metohde inquiry students X IPA 1 SMA 3 Metro. Methode observation, documents, and interview. Tecniqe of data tes and non tes. Enhancement skill write tex anekdot praciclus I total presentase 47,38%, and learning achievement praciclus 46 to cyclus I or 66, increased 20%. Cyclus II enhancement skill write tex anekdot or 97,68%, increased as 50,30%, and learning achievement 75, increased 9%. Cyclus III enhancement skill write tex anekdot 65,69%, increased 31,99%, and learning achievement 85, increased 10%. Conclusion inquiry method to enhancement skill write tex anekdot increased of significant from pracyclus, cyclus I, cyclus II and cyclus III, especially write tex anekdot.